2010
DOI: 10.1097/bor.0b013e32833d20ae
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between joint shape and the development of osteoarthritis

Abstract: Purpose of review To present an updated summary of the relationship between joint shape and the development of osteoarthritis, with a particular focus on osteoarthritis of the hip. Recent findings Osteoarthritis of the hip is highly heritable, with a genetic contribution estimated at 60%. Among the genes that have been linked to this disease are several that are involved in the development and maintenance of joint shape, including members of the Wingless (Wnt) and the bone morphogenetic protein (BMP) family.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 81 publications
3
59
1
2
Order By: Relevance
“…The simplest of these is via increased BMD itself, termed 'mediated' pleiotropy. 72 Alternatively, BMD genes could directly influence other phenotypes that in turn increase the risk of developing OA ('biological' pleiotropy 72 ), such as cartilage thickness or joint shape; 73 these characteristics have been termed 'endophenotypes', and their study could help clarify relevant mechanisms. 74 For example, a variant allele in the DOT1L gene has been associated with increased cartilage thickness (measured as joint space width) and a decreased risk of hip OA.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 99%
“…The simplest of these is via increased BMD itself, termed 'mediated' pleiotropy. 72 Alternatively, BMD genes could directly influence other phenotypes that in turn increase the risk of developing OA ('biological' pleiotropy 72 ), such as cartilage thickness or joint shape; 73 these characteristics have been termed 'endophenotypes', and their study could help clarify relevant mechanisms. 74 For example, a variant allele in the DOT1L gene has been associated with increased cartilage thickness (measured as joint space width) and a decreased risk of hip OA.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 99%
“…Cohort studies have demonstrated that after age, obesity and metabolic disease are major risk factors for the development of OA (4,5). OA is now generally accepted to be an inflammatory and biomechanical whole-organ disease that is influenced by a number of factors including joint shape and dysplasia (6), obesity (7), synovitis (8-10), complement proteins (11), systemic inflammatory mediators (1,12), inflammaging (13,14), innate immunity (15), the low-grade inflammation (16) induced by metabolic syndrome (1,17) and diabetes mellitus (18). However, despite the fact that all joint tissues are potentially implicated in disease initiation and progression in OA, it is the articular cartilage component that has received the most attention in the context of aging, injury and disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Chociaż sama chrząstka nie może zabsorbować całej energii oddziałującej na nią podczas ruchu, to dzięki swojej budowie pod wpływem obciążeń podlega ona odwracalnym deformacjom rozpraszającym energię oraz przekazuje ją dalej -w kierunku bardziej odpornej mechanicznie kości podchrzęstnej. Skuteczność rozpraszania i przekazywania energii przez chrząstkę zależy w dużej mierze od prawidłowej budowy stawu, a wszelkie nieprawidłowości dotyczące tych czynników znacznie przyczyniają się do przyspieszenia rozwoju zmian zwyrodnieniowych [5].…”
Section: Wstępunclassified
“…Starzejące się chondrocyty tracą aktywność syntetyczną, czego efektem jest produkcja mniejszych i nieregularnych cząsteczek agrekanów oraz obniżenie zdolności utrzymania homeostazy chrząst-ki stawowej. Procesy starzenia chrząstki nie muszą prowadzić nieuchronnie do rozwoju osteoartrozy, jednak zachodzące w niej zmiany związane z wiekiem dają podstawy do rozwoju choroby, szczególnie jeśli występują dodatkowe czynniki ryzyka, zwłaszcza nieprawidłowa budowa stawu [5].…”
Section: Wstępunclassified